"Night with the General" - a Democratic Documentary - Piepiórka, Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The film is one of few examples of political documentaries produced in Poland after 1989. It is not limited to merely outlining the political argument over General Jaruzelski’s decision to impose martial law. Although it concerns events in Polish history, it is not a historical documentary, as it brings forth present-day political conflicts that have arisen around historical events. Trying to reconstruct this current political argument, Zmarz-Koczanowicz reaches for a method developed in the 1970s by the so-called “Kraków School” led by Krzysztof Kieślowski. ^e “talking heads” method was meant to help documentary filmmakers in the Polish People’s Republic reach what the person in the street actually thought and avoid the distortions of propaganda. For Kieślowski, however, the overriding aim was conciliation and an attempt to understand both sides of the political barricade - the authorities and the vox popu- li. His attitude, according to the terminology suggested by Chantal Mouffe, was a post-political one striving for an agreement through a rational dialogue. Zmarz-Koczanowicz’s aim, however, is different: she is intent on showing a clash of different hegemonies that do not strive for consensus. Their agonistic argument, played out in the political register, rather than a moral one, is a guarantee, according to this Belgian philosopher of politics, that democracy will continue to exist.